IMPLEMENTASI METODE DRILL AND PRACTICE DALAM MENINGKATKAN KEMAMPUAN MEMBACA AL-QUR’AN SISWA PADA MATA PELAJARAN AL-QUR’AN HADITS DI MADRASAH TSANAWIYAH NEGERI 8 MUARO JAMBI - Shevi Yani; Neneng Hasanah (STKIP Pesisir Selatan, 2025)
This research is motivated by the low ability of students to read the Qur'an in reading the Qur'an in the Qur'an lesson at the State Islamic Junior High School 8 Muaro Jambi. Among the identified challenges are students’ difficulties in achieving fluency, errors in pronouncing makharijul huruf, and insufficient usage of tajwid rules. Therefore, there is a need for an effective and suitable learning approach to enhance students’ Qur’anic reading abilities. The purpose of this research is to detail the implementation of the drill and practice technique to improve students’ Qur’anic reading skills in the Al-Qur’an Hadith subject at Madrasah Tsanawiyah Negeri 8 Muaro Jambi. This research uses a qualitative approach with a descriptive research type. Data collection was carried out through observation, in-depth interviews with Al-Qur’an Hadith educators, the principal of the school, and students, along with documentation. Informants were selected through purposive sampling, focusing on those who are directly engaged and knowledgeable about the educational process. Findings from the study reveal that the drill and practice method was carried out using structured and repetitive reading exercises of the Qur’an, establishment of a reading routine of verses at the start of lessons, practice on makharijul huruf and tajwid, and timely feedback from the teacher. This approach was additionally supported through consistent practice.